Exploring the implication of changes in forest cover on sago nutrients: insights from monitoring in selected regions of Papua, Indonesia - Fetriyuna, Fetriyuna; Purwestri, Ratna Chrismiari; Letsoin, Sri Murniani Angelina; Jati, Ignasius Radix A. P.; Rahmawan, Fajar; Wirawan, Nia Novita; Setiawan, Budhi; Hájek, Miroslav; Herák, David (Frontiers in Forests and Global Change, 2025)
Sago (Metroxylon spp.), a traditional staple food that naturally grows in Papuan forests, plays a vital role in the food security of local inhabitants and is equally important in food and non-food industries. Changes in forest cover to other land uses might lead to shifts in the sago ecosystem, which could also affect sago production and nutrients. Currently, there is a lack of studies correlating vegetation changes and nutrient profiles. This research article aims to explore the vegetation area changes and their potential relationship to the sago forest ecosystem and nutrient profiles of the sago. NDVI information was collected from Mappi and Merauke Regency, Papua Province of Indonesia in 1990, 1996, 2012, 2018, and 2020. Sago samples were gathered from selected sites in Mappi and Merauke. No statistically significant changes in NDVI degradation classes or sago habitat area classifications were observed over the years in each regency. NDVI degradation classes in Merauke showed a significantly higher proportion of degraded areas (>76%) and a more pronounced yellowish color than in Mappi (8%). Approximately 90% of areas in Mappi were categorized as having an increase in trees and no degradation, which was significantly higher than in Merauke (<5%). Sago in Merauke exhibited significantly higher macro and micronutrient content than Mappi. Findings from GLM predictor analysis showed that higher carbohydrate, protein, Ca, Cu, Mg, and Na content of sago samples were positively and significantly associated with collected samples in Merauke. An increase in carbohydrate levels was also positively associated with a higher percentage of NDVI classes related to the yellowish color. The results indicated that sago palms in Merauke are more mature, and therefore, the samples were harvested at an older age than those in Mappi. NDVI can be used to monitor area degradation and predict nutritional quality.